1992
DOI: 10.1159/000172081
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Colectomy in the Management of Acutely Obstructed Left Colon Cancer

Abstract: One-stage subtotal colectomy of an acutely obstructed colon would improve quality of life while shortening the length of hospitalization. Prohibitive surgical risks, though, are commonly ascribed to such an approach. Analyzing the senior author’s experience we compared the one-stage approach versus multistaged resection concerning operative mortality and morbidity rates and the duration of hospital stay. Forty-nine out of 291 (17%) large bowel cancer patients presented with acute left-sided obstruction requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…2). Six studies demonstrated similar results between the two groups 12,13,22,26,30,31 . Only Huddy et al 23 reported, in a relatively small (42 patients) and methodologically poor study, that results were better for two-or three-stage procedures.…”
Section: One-stage Proceduresmentioning
confidence: 80%
See 2 more Smart Citations
“…2). Six studies demonstrated similar results between the two groups 12,13,22,26,30,31 . Only Huddy et al 23 reported, in a relatively small (42 patients) and methodologically poor study, that results were better for two-or three-stage procedures.…”
Section: One-stage Proceduresmentioning
confidence: 80%
“…4). The randomized Subtotal Colectomy versus On- Table Irrigation (11) Huddy et al 23 1 of 27 (4) 6 of 15 (40) Stephenson et al 29 2 of 15 (13) 1 of 34 (3) de Almeida et al 22 1 of 11 (9) 2 of 20 (10) Runkel et al 13 1 of 6 (17) 3 of 21 (14) Kasperk et al 24 34 of 102 (33) 7 of 32 (22) Mochizuki et al 27 2 of 11 (18) 1 of 44 (2) Lau et al 25 3 of 9 (33) 2 of 35 (6) Turan et al (0) Zorcolo et al 33 6 of 24 (25) 6 of 93 (6) Meyer et al 26 34 of 268 (13) 38 of 358 (11) Villar et al 31 1 of 20 (5) 2 of 43 (5) Poon et al (Fig. 5).…”
Section: One-stage Proceduresmentioning
confidence: 99%
See 1 more Smart Citation